Longitudinal changes in children with autism spectrum disorder receiving applied behavior analysis or early start denver model interventions over six months - Du, Yusang; Yang, Xiaozhen; Wang, MengMeng; Lv, QianQian; Zhou, Hui; Sang, Gao (Frontiers in Pediatrics, 2025)
BackgroundAutism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder characterized by social communication difficulties, restricted interests, repetitive behaviors, and sensory abnormalities. The rising prevalence of ASD presents a significant public health concern, with no pharmacological treatments available for its core symptoms. Therefore, early and effective behavioral interventions are crucial to improving developmental outcomes for children with ASD. Current interventions primarily focus on educational rehabilitation methods, including Applied behavior Analysis (ABA) and the Early Start Denver Model (ESDM).ObjectiveThis study aims to examine the developmental changes in children with ASD following six months of ABA therapy or ESDM intervention.MethodsFrom December 2021 to December 2023, 30 children receiving ABA therapy at the Zhejiang Rehabilitation Medical Center (40 min/session, 4 sessions/day, 5 days/week), while another 30 children undergoing ESDM training at Hangzhou Children's Hospital (2 h of one-on-one sessions and 0.5 h of group sessions/day, 5 days/week). Both groups participated in their respective interventions for six months. Pre- and post-treatment assessments were conducted using the Psycho-educational Profile-Third Edition (PEP-3).ResultsBoth groups showed significant improvements in PEP-3 scores post-treatment, including cognitive verbal/pre-verbal, expressive language, receptive language, social reciprocity, small muscles, imitation, emotional expression, and verbal and nonverbal behavioral characteristics.ConclusionBoth ABA and ESDM interventions were associated with comprehensive improvements in children with ASD over a six-month period.